Elaboración de crema cicatrizante a base de romero (Rosmarinus officinalis) y llantén (Plantago major), Machala 2014 - Reyes García, Karina P. (2014)
Since ancient times they have been use more frequently and medicinal plants due to technological development and give due importance to medicinal plants. Because most people use chemical medications that cause us harm. In homes and medicinal plants are grown not because it has lost the habit of using natural as the lack of time , or the lack of use of medicinal plants.